Effect of Subsurface Drip Irrigation on Soil Desalination and Soil Fungal Communities in Saline–Alkaline Sunflower Fields - Jiapeng Zhang; Dongmei Qiao; Dongliang Zhang; Zhaonan Chi; Xueqin Fan; Lixia Cao; Weiping Li (Agronomy)
A field experiment was conducted on sunflowers in a mild-to-moderate saline–alkaline area in the Tumochuan Plain irrigation region in China. The experimental design included using surface drip irrigation as a control (CK) and four subsurface drip irrigation treatments at burial depths of 10 cm (D10), 15 cm (D15), 20 cm (D20), and 25 cm (D25) to analyze the effect of the drip irrigation belt burial depth on soil physicochemical properties and soil desalination in the main root zone of saline–alkaline sunflower farmland. Based on macro-genome sequencing technology, the diversity, composition, and structure of soil fungal communities in the main root zone were revealed in response to the depth of drip irrigation. The results show that subsurface drip irrigation treatments improved soil desalination with rates ranging from 15.33% to 26.96%. The D25 treatment achieved an 82.01% higher desalination rate than CK and outperformed D10, D15, and D20 by 43.35%, 13.43%, and 24.89%, respectively, demonstrating the most effective desalination with a 25 cm burial depth under the same water and fertilizer management conditions. Additionally, subsurface drip irrigation enhanced the diversity and abundance of soil fungal communities; the Shannon indices for D15 and D20 were 8.1% and 12.3% higher than that of CK, respectively, whereas the Chao1 indices increased by 21.2% and 17.4%, respectively. During the budding stage, the fungal community in the main root zone (20–40 cm) was dominated by Ascomycetes and Tephritobacterium, with Alternaria being the predominant genus. Notably, the relative abundance of Ascomycetes was 118.8% higher in D25 than in CK. Structural equation modeling quantified the relationships between soil physicochemical properties, with an SMC of 0.94, indicating a model fit within an acceptable range. An SEM analysis revealed that the soil water content (SWC), soil EC, and soil NO3−-N exerted the most significant combined effect on soil fungal composition and diversity. This study examined the effects of the drip irrigation tape burial depth on soil physicochemical characteristics, the fungal community structure, and diversity in the main root zone (20–40 cm) of saline–alkaline sunflower fields under subsurface drip irrigation. This study aims to provide theoretical support for water-saving agricultural practices in saline–alkaline soils. We developed a subsurface drip irrigation method for sunflowers in the lightly to moderately saline–alkaline land in the irrigation area of China’s Tumochuan Plain, and the suitable depth of burial of the drip irrigation belt was 25 cm.